PENGARUH MEDIA INTERAKTIF ANIMASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS V SDN GONDRONG 2 - Krisdayanti; Ino Budiatman; Nurul Muttaqien (STKIP Subang, 2023)
This study aims to determine whether or not there is an influence of interactive animated media on student learning outcomes in science subjects. The method used in this study is Quasi Experimental and Conventional. The hypothesis put forward in this study is: